The Role of Principal Leadership Style in Enhancing 21st-Century Teaching Skills: Evidence from Indonesian Pri-mary Schools - Wawan Kurniawan; Syarifuddin Syarifuddin; Muh. Fahreza W (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study explores the role of principal leadership style in shaping the quality of 21st-century teaching skills among elementary school teachers in Indonesia, with particular attention to leadership practices, challenges encountered, and strategies for improvement. Using a descriptive qualitative approach, the research was conducted at SD Negeri 90 Sampulungan, Takalar, South Sulawesi, involving the principal and teachers as participants. Data were gathered through in-depth interviews, direct observations, and documentation to provide a comprehensive understanding of the phenomenon. The findings indicate that the principal primarily employed transformational and democratic leadership styles. These approaches motivated teachers by inspiring them with clear visions, serving as role models, and encouraging active participation in decision-making processes. Such leadership practices contributed significantly to teacher engagement and the overall school climate. Teachers, in turn, demonstrated competencies aligned with 21st-century learning demands, particularly through the application of the 4Cs: critical thinking, creativity, communication, and collaboration. They also showed efforts in integrating information and communication technology (ICT) into their teaching practices and implementing interactive classroom management strategies. However, several challenges were identified, including limited availability of facilities, resistance among some teachers toward adopting innovative methods, and the heavy administrative workload that often distracted from instructional focus. To address these issues, the principal implemented various strategies such as organizing continuous professional development training, providing close supervision and mentoring, and offering motivational support to sustain teacher commitment. Overall, the study emphasizes the crucial role of transformational leadership in strengthening teachers’ 21st-century skills and offers practical implications for educational policy development, while also recommending future studies across broader school contexts in Indonesia.